2004
DOI: 10.1038/modpathol.3800148
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal immunophenotype in adenocarcinomas of the uterine cervix and related glandular lesions: a possible link between lobular endocervical glandular hyperplasia/pyloric gland metaplasia and ‘adenoma malignum‘

Abstract: Gastrointestinal phenotype in cervical adenocarcinomas was examined by immunohistochemistry and correlated with morphologic features. Antibody panels included anti-MUC2, MUC6, CD10, chromogranin A (CGA) and HIK1083. In addition, expression of p16 INK4 , a cyclin-dependent kinase inhibitor which is expressed in a variety of high-risk HPV-related conditions, was studied. A total of 94 invasive adenocarcinomas including 20 minimal deviation adenocarcinomas (MDAs) and 72 adenocarcinomas in situ (AIS) were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
210
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(214 citation statements)
references
References 26 publications
4
210
0
Order By: Relevance
“…Therefore, a differential diagnosis between LEGH and MDA is challenging. Although LEGH was first reported as a benign disease, it has been reported as a precursor of MDA, because of frequent association between LEGH and MDA as well as its genetic characteristics 6, 7, 8, 9, 10, 11. We previously reported that some LEGH lesions were a precancerous form of MDA due to the pattern of X chromosome inactivation using the human androgen receptor (HUMARA) method 12.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a differential diagnosis between LEGH and MDA is challenging. Although LEGH was first reported as a benign disease, it has been reported as a precursor of MDA, because of frequent association between LEGH and MDA as well as its genetic characteristics 6, 7, 8, 9, 10, 11. We previously reported that some LEGH lesions were a precancerous form of MDA due to the pattern of X chromosome inactivation using the human androgen receptor (HUMARA) method 12.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Additionally, both neoplasms can be associated with lobular endocervical glandular hyperplasia (LEGH), 19 which represents a pyloric gland metaplasia 21 and has also been shown to be hr-HPV DNA-negative. 16,22 These facts suggest that the mucinous AC with gastric immunophenotype, incorporating MDA as its well-differentiated form in the morphological spectrum, is a distinct entity arising via a hr-HPV-independent pathway.…”
mentioning
confidence: 99%
“…In a previous investigation we demonstrated that mucinous AC with gastric immunophenotype was morphologically distinct with a good interobserver reproducibility, characterized by neoplastic cells with conspicuous cell borders and clear and/or pale eosinophilic voluminous cytoplasm, and aggressive clinical behavior. 20,23 MDA is not a common neoplasm, accounting for 1-3% of all endocervical ACs, but the gastric-type adenocarcinoma (GAC) appears in 10 -30% of all endocervical ACs 19,20 and thus may not be a negligible pitfall of HPV DNA tests and vaccination, and therapeutic strategy.…”
mentioning
confidence: 99%
“…Histological changes mimicking clear cell carcinoma have been reported after neoadjuvant therapy but immunohistochemical positive expression of cEa, cytokeratin 7 (diffuse), and cytokeratin 20 (focal), positive HIk1083 stain or negative/focal p16 stain favors gastric-type mucinous adenocarcinoma of the cervix (12). Immunophenotypic overlap with pancreaticobiliary adenocarcinomas exists but PaX8 immunoreactivity may be useful to distinguish them.…”
Section: Discussionmentioning
confidence: 99%